Iconicizing Kingship in Elizabethan England: Strategic Acting by Queen Elizabeth I - Kizelbach, Urszula (Studia Anglica Posnaniensia, 2013)
Renaissance England is often discussed in the context of theatre and theatrical acting. The fact is that Renaissance monarchs, too, viewed kingship in terms of theatrical display and public performance. Such is the nature of royalty presented by King James I in Basilicon Doron. Queen Elizabeth I was playing all her life. Faced with the problem of her femininity in the world of men, as well as her ambivalent hereditary rights as a member of the Tudor dynasty, she focused on legitimizing her reign through playing different roles - she played the fearful king, the loving queen, she even played Virgin Mary. But Elizabeth emerges as the most stunning actress when she plays herself. On her summer visit to Wanstead in 1578 she took an active part in the pageant “The lady of May”, playing herself, “Good Queen Bess”, which Sir Philip Sidney depicted in his pastoral romance The lady of May. In this way, Elizabeth became her own icon. This paper provides instances of the Queen’s political role play in a historical and socio-cultural context of the time.